2013
DOI: 10.3109/0142159x.2012.756576
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on trainees’ and supervisors’ perceptions of assessment for learning in postgraduate medical education

Abstract: Introduction: Recent changes in postgraduate medical training curricula usually encompass a shift towards more formative assessment, or assessment for learning. However, though theoretically well suited to postgraduate training, evidence is emerging that engaging in formative assessment in daily clinical practice is complex. Aim: We aimed to explore trainees' and supervisors' perceptions of what factors determine active engagement in formative assessment. Methods: Focus group study with postgraduate trainees a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 49 publications
7
70
0
Order By: Relevance
“…This led to a situationally bound assessment of the potential costs and merits of getting feedback, which in turn influenced the timing, topic, source, and method of feedback-seeking. A study on the level of active engagement in formative assessment by trainees and supervisors, added the credibility of feedback to the list of influences and also found that supportiveness of the learning environment was important for feedback facilitation (Dijksterhuis et al 2013). These findings are corroborated by what other researchers have found (Sargeant et al 2005(Sargeant et al , 2011Watling et al 2012).…”
Section: Learning Learners and Labelsmentioning
confidence: 51%
“…This led to a situationally bound assessment of the potential costs and merits of getting feedback, which in turn influenced the timing, topic, source, and method of feedback-seeking. A study on the level of active engagement in formative assessment by trainees and supervisors, added the credibility of feedback to the list of influences and also found that supportiveness of the learning environment was important for feedback facilitation (Dijksterhuis et al 2013). These findings are corroborated by what other researchers have found (Sargeant et al 2005(Sargeant et al , 2011Watling et al 2012).…”
Section: Learning Learners and Labelsmentioning
confidence: 51%
“…Consistent with prior studies, participants in our focus groups described the importance of teachers creating a safe environment for feedback. 18,23 Residents also described the importance of the learner in feedback-seeking; specifically, the learner who critically reflected on his or her performance, and demonstrated openness and engagement to feedback, facilitated effective feedback processes. 24,25 While our residents described the importance of continuity in a teacher-learner relationship, they pointed out that logistics and the competing tasks of patient care and education often left little time for feedback.…”
Section: Discussionmentioning
confidence: 99%
“…5,15 Yet the effectiveness of feedback and its subsequent impact on learning are thought to increase when learners and supervisors engage in meaningful relationships over time and when learners receive credible feedback, which is more likely to occur when learners have an opportunity to demonstrate improvement. 16 This heightens the importance of developing strategies to provide students with opportunities to progress in the current inpatient environment. Some students in our study described experiences in which they thought they did grow as physicians, when attending physicians found ways to establish a relationship with them and provide meaningful feedback in the short period of time they spent together.…”
Section: Discussionmentioning
confidence: 99%